IN VITRO ANTIMICROBIAL ACTIVITY OF CEREULIDE AND VALINOMYCIN COMPARE WITH CYCLIC D,L- α –PEPTIDES AND THEIR ENHANCED EFFECT - ARTHIT MAKARASEN; NANTHAWAN REUK-NGAM; PIYACHAT CHUYSINUAN; CHAIYAWAT AONSRI; NITIRAT CHIMNOI; MINORU ISOBE; SUPANNA TECHASAKUL (International Journal of Pharma and Bio Sciences, 2015)
Cereulide and valinomycin are both cyclic depsipeptides with 12 stereogenic centers that have a very similar sequence in the structure. Both compounds are hexagonal cylinder-like framework and all the side chains stick outside of the framework. The framework of cyclic D,L-α-peptides were structured different from the cereulide and valinomycin which are performed by cyclic DDLL-peptides. The cyclic D,L-α-peptides consisted of an even number of alternating D- and L- α-amino acid which can adopt flat and stack to form hollow, b-sheet like tubular structures. The amino acid side chains are presented on the outside surface of the framework and the interior surface of such a tube is hydrophilic. In our studies, we found that the original cereulide and valinomycin demonstrated higher antimicrobial activity than the cyclic D,L-α-peptides which are synthesized by using cereulide and valinomycin as a model structure. Furthermore, the combinations of cereulide or valinomycin with clinically used drugs against fungi were found to enhance the antimicrobial efficacy by decreasing the MIC values between 2-128 times.